Creativity in magazines - Braspenning, Esther (Henry Stewart Talks, 2009)
Creativity in print has always been a bigger challenge than on TV and more recently digital, Relevance and control, Print engagement study, Attracting attention, Size of the ad and positioning, Creative formats, Female and male reaction to magazine advertising
Archived at 2022/11/27